Treatment of Helicobacter pylori Infection in Korea: A Systematic Review and Meta-analysis - Lee, Sang Wook (J Korean Med Sci, 2015)
The efficacy of seven-day clarithromycin-based standard triple therapy (STT) for Helicobacter pylori has decreased in Korea over the past decade. The aim of this meta-analysis was to clarify the efficacy of first-line and second-line therapies in Korea. This systematic review will provide an overview of H. pylori eradication and present new therapeutic strategies used in Korea. An extensive search of the literature concerning STT, sequential therapy (SET), concomitant therapy (CT), bismuth-containing quadruple therapy (BCQT) and various other therapies used in Korea was performed. All selected studies were randomized controlled trials (RCTs). Eighteen RCTs were eligible for systematic review. The alternative regimens comparing seven-day STT as a first-line therapy include SET, CT, levofloxacin-based therapy (LBT), BCQT, and STT with prolonged duration. The results of the meta-analysis suggest that SET is superior to seven-day STT. The overall eradication rate by intention to treat (ITT) analysis was 69.8% for STT and 79.7% for SET. The overall eradication rate by per-protocol (PP) analysis was 77.0% for STT and 85.0% for SET. The odds ratios for the ITT and PP eradication rate were 0.57 (95% confidence interval [CI], 0.43 to 0.74) and 0.52 (95% CI, 0.35 to 0.76), respectively. In the subgroup analysis, however, there were no significant differences between SET and STT with prolonged durations. Alternative regimens to seven-day BCQT as second-line therapy include LBT, moxifloxacin-based therapy and 14-day BCQT. The eradication rates of these alternative regimens were not superior to that of the conventional treatment. SET is superior to seven-day STT but not to STT with prolonged duration. GRAPHICAL ABSTRACT: [Image: see text]